Ocorrência de formigas Acromyrmex Mayr, 1865, em alguns municípios do Brasil - Rando, Jael Simões Santos; Fort, Luiz Carlos [UNESP] (Universidade Estadual de Maringa, 2005)
It were collected species of Acromyrmex Mayr, 1865 in many brazilian cities from Santa Catarina, Paraná, São Paulo, Minas Gerais, Goiás, Mato Grosso do Sul, Mato Grosso, Rondônia and Amapá states and in Paraguay and Uruguay, with the purpose to bring up-to-date their occurrence. Specimens collected on trips were identified at laboratory of Fca/Unesp/Botucatu-SP. It were recorded, for the first time, the occurrence of A. rugosus rugosus (F. Smith, 1858) in Paraná, Rondônia and Santa Catarina states; A. subterraneus subterraneus (Forel, 1893) in Amapá and Bahia; A. diasi Gonçalves, 1982 in Rio Grande do Sul and Paraná states; A. coronatus (Fabricius, 1804) in Paraná; A. balzani (Emery, 1890) in Amapá and A. subterranens brunneus (Forel, 1911) in Goiás.
Occurrence of ants Acromyrmex Mayr, 1865 in some cities of Brasil
Keywords: Acromyrmex; Geographical distribution; Leaf-cutting ants; ant; Brazil; city; geographic distribution; leaf cutting ant; nonhuman; Paraguay; species distribution; Uruguay; Acromyrmex balzani; Acromyrmex coronatus; Acromyrmex diasi; Acromyrmex rugosus rugosus; Acromyrmex subterraneus subterraneus; Atta; Formicidae